7 - Les immigrés nigérians à Douala: problèmes et stratégies d’insertion sociale des étrangers en milieu urbain: 10.4314/ad.v28i2.22180 - Nkene, Blaise-Jacques (Africa Development, 2003)
Despised and rejected by the local populations in the city of Douala, allegedly because of their arrogance and ostentation, Nigerian migrants have resorted to a set of individual and collective micro strategies, for their own social integra tion, despite the rejection from which they are suffering. This paradoxical socio logical configuration is at the heart of this study. It describes a specific kind of interaction between nationals and non-nationals in an urban environment and also engages the construction of the othemess in the problematic of African international migration.